Neoconstitucionalismo negativo y neoconstitucionalismo positivo - Giovanni Battista Ratti (Universidad Hemisferios, 2014)
The term “neoconstitucionalism” is quite ambiguous: contemporary culture uses it to denote such as heterogeneous things as a form of state, a policy of judicial activism, a theoretical account of contemporary legal systems, a kind of legal methodology, and ideological adherence to the law. This paper focuses on the aspects related to judicial policy, legal theory and legal methodology, by emphasizing two possible perspectives. The first one called negative, that delineates such a prismatic conception of law as a set of oppositions to the theses defended by predominant legal theories. The second one is dubbed positive, since it claims to having identified a whole series of “new discoveries” about contemporary legal systems. The positive version is characterized by eight points: (1) the law of constitutional state is a combination of rules and principles, (2) rules and principles are liable to bring about a systematic set of norms, (3) contemporary constitutions incorporate moral values, so that they have created a relevant connection between law and morality, (4) the incorporation of moral values ​​in the constitution means that the interpreters must construe the constitutional provisions by a moral reading, (5) any legal norm is defeasable, (6) some legal standards require balancing, as opposed to traditional subsuntive reasoning, (7) by holistically interpreting legal provisions, judges can decide any dispute whatsoever, (8) legal norms cannot have any content, since their content is eventually determined by moral judgments. The paper winds up illustrating some of the achievements and the shortcomings of each kind of neoconstitutionalism.